Registration of new potential bone marrow donors: experience in the interior of Pernambuco - Alexandre, Ana Carla Silva; Santos, Cíntia Taísa Ferreira; Silva, Girleide Isídio da; Limeira, Jhenyff de Barros Remigio; SILVA, VANIA RIBEIRO DE HOLANDA (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2022)
Objective: To report the experience of nursing students in an extension project to capture and raise awareness of potential bone marrow donors. Methods: This is an experience report resulting from actions carried out by an extension project. The actions took place in Pesqueira, Pernambuco, Brazil, held in three events between March and May 2019. The sample consisted of 369 new potential bone marrow donors. Results: The first intervention totaled 54 health professionals, in the second, 248 records were obtained in the general population. The last intervention provided a total of 67 student registrations. Final Considerations: The actions promoted reflections, in addition to raising awareness and attracting new potential donors, for doing something not yet seen in the city, showed that extension is a fundamental tool to carry out the exchange of values between the university and the community.